The Politics of Land, Consent, and Negotiation: Revisiting the Development-Displacement Narratives from Singur in West Bengal - Ritanjan Das (South Asia Multidisciplinary Academic Journal, 2016)
India’s rapid economic growth has frequently been marred by struggles over land acquisition and displacement. This paper re-examines one such case. In 2006, protests erupted in Singur (a small cluster of villages in West Bengal) against government initiatives to acquire land for a private industrial project. The protests gathered enough momentum to stall the project, and went on to have a decisive impact on the electoral fortunes of the government, thus attaining a cult status in the country’s development-displacement narratives. This paper presents the Singur story in a new light, arguing that there was a political character to the entire episode, largely ignored by mainstream literature. Based on the idea of the ‘shadow-state’ (Harriss-White 2003), the paper examines the role played by the political managers of the ruling Communist Party of India (Marxist)—CPI(M)—and highlights three themes—choice of land, acquiring consent, and negotiation—to build its narrative.